Linkages between education expenditure and economic growth: evidence from 'CHINDIA' - Kaur, Harpaljit; Abdul Hamid, Baharom; Habibullah, Muzafar Shah (2014)
This paper examines the relationship between education expenditure and economic growth in China and India by employing annual data from 1970 to 2005. This study utilizes multi econometric tools such as the Johansen-Juselius (1990) co-integration test, Ordinary Least Square (OLS) method, Dynamic Ordinary Least Square (DOLS), Vector Error Correction Model (VECM) as well as variance decomposition to obtain a robust and consistent result. The findings indicate that there exists a long run trending relationship between income level (Gross Domestic Product per capita (GDPpc) and education expenditure in both China and India. In the long run, a unidirectional causal relationship could be detected for both countries, running from income level to education expenditure for the case of China, while for the case of India education expenditure Granger causes income level. The results are robust and consistent across all methods.